The choice of the number of processing channels in the radiomonitoring equipment on the basis of adaptive multibeam antenna arrays - S. V. Kozlov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Using mathematical modeling the angle-frequency characteristics of the beams and the accuracy of direction finding of the useful signal in an adaptive multibeam antenna arrays (AMLAR) with spatial compensation of noise and sum-difference processing are investigated. It's shown that the required number of generated spatial channels for AMLAR is approximately twice as large as in MLAR without adaptive processing. The nature of dependence of the maximum displacement of the total and zero difference channel of the beam on the deviation of the frequency of the received signal from the reference, for which the vectors of the weighting coefficients are formed at spatial noise compensation and digital diagrams. It's shown that the broadband AMLAR is actually limited by the deviation of the frequency at which there are significant changes in the amplitude diagrams of the direction of the receiving elements.